2008
DOI: 10.1126/science.1165395
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Loss of microRNA-101 Leads to Overexpression of Histone Methyltransferase EZH2 in Cancer

Abstract: Enhancer of zeste homolog 2 (EZH2) is a mammalian histone methyltransferase that contributes to the epigenetic silencing of target genes and that regulates the survival and metastasis of cancer cells. EZH2 is overexpressed in aggressive solid tumors by mechanisms that remain unclear. Here, we show that the expression and function of EZH2 in cancer cell lines is inhibited by microRNA-101 (miR-101). Analysis of human prostate tumors revealed that miR-101 expression decreases during cancer progression, parallelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
786
2
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 967 publications
(848 citation statements)
references
References 27 publications
48
786
2
6
Order By: Relevance
“…The protumorigenic and prometastatic miRNA miR-19b was upregulated in metastatic cells (Table 2), whereas the antimetastatic miR-16 was downregulated in lung metastatic cells (Table 3) (Hurst et al, 2009). However, there were few exceptions: metastatic cells expressed elevated levels of miR-101, which has been described as tumor suppressor in other cancer types (Varambally et al, 2008). In summary, we have described results that suggest a role for miRNAs in changing the protein expression pattern in cancer cells depending on the site of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The protumorigenic and prometastatic miRNA miR-19b was upregulated in metastatic cells (Table 2), whereas the antimetastatic miR-16 was downregulated in lung metastatic cells (Table 3) (Hurst et al, 2009). However, there were few exceptions: metastatic cells expressed elevated levels of miR-101, which has been described as tumor suppressor in other cancer types (Varambally et al, 2008). In summary, we have described results that suggest a role for miRNAs in changing the protein expression pattern in cancer cells depending on the site of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, H3K27 methylation has been shown to mark genes for de novo methylation in cancer (Schlesinger et al, 2007). A recent study found that frequent overexpression of EZH2 in aggressive solid tumors is largely due to the loss of its regulator microRNA-101 (Varambally et al, 2008). More specifically, reintroduction of miR-101 or knockdown of EZH2 expression was sufficient to reduce H3K27 trimethylation and increase RUNX3 mRNA levels.…”
Section: Putative Causes Of Runx3 Hypermethylationmentioning
confidence: 99%
“…miR-148 repressed expression of DNMT3B through binding with high homology to the region of the coding sequence of the DNMT3B transcript, but the mechanism remained unclear. In contrast to miR-148a, miR-101 modulates cancer epigenetics by repressing the polycomb group protein EZH2, which contributes to the epigenetic silencing of target genes and regulates the survival and metastasis of cancer cells (Varambally et al, 2008;Friedman et al, 2009). Not only does miR-101 suppress the expression and function of EZH2 in cancer cell lines but also there is an inverse correlation between miR-101 expression and EZH2 expression during cancer progression in human prostate tumors (Varambally et al, 2008).…”
Section: Microrna and Metastasis H Zhang Et Almentioning
confidence: 99%
“…In contrast to miR-148a, miR-101 modulates cancer epigenetics by repressing the polycomb group protein EZH2, which contributes to the epigenetic silencing of target genes and regulates the survival and metastasis of cancer cells (Varambally et al, 2008;Friedman et al, 2009). Not only does miR-101 suppress the expression and function of EZH2 in cancer cell lines but also there is an inverse correlation between miR-101 expression and EZH2 expression during cancer progression in human prostate tumors (Varambally et al, 2008). Varambally et al (2008) found that loss of one or the other of the two genomic loci of miR-101 occurred more frequently in metastatic tumor cells.…”
Section: Microrna and Metastasis H Zhang Et Almentioning
confidence: 99%
See 1 more Smart Citation